Team for survival – only a shared vision can save lives Thesis 5 of the Bad Boll Resuscitation and Emergency Talks 2023 Team for survival – nur die gemeinsame Vision kann Leben retten These 5 der Bad Boller Reanimations- und Notfallgespräche 2023 - Ramshorn-Zimmer, A.; Bohn, A.; Dormann, H.; Wolcke, B.; Wurmb, T.; Gräsner, J. T. (Anästhesiologie & Intensivmedizin, 2023)
Cardiopulmonary resuscitation is not an isolated therapeutic measure, but a complex, interdisciplinary and interprofessional care process that not only integrates the entire portfolio of acute medical care, but instantly also numerous actors in the care chain, from the actual patient treatment to the strategic-dispositive decision elements and psychosocial intervention measures. Responsibility is actively assumed and shared together in the team.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Bad Boll Resuscitation and Emergency Talks; Cardiac Arrest; Interprofessional Care; Mental Health; Teamwork